CORRELATION AND PATH ANALYSIS FOR CLUSTERBEAN VEGETABLE POD YIELD - P. SHABARISH RAI; P. R. DHARMATTI (The Bioscan, 2014)
Study was conducted mainly using clusterbean lines collected around North Karnataka area of India. This study helps in identifying the characters which mainly contributing to the pod yield. Thirty one genotypes of clusterbean were evaluated during rainy season 2009 and observations recorded on growth and vegetable pod yield parameters. Correlation studies indicated positive associations of vegetable pod yield per hectare (t) with plant height (0.315, 0.309), pods per cluster (0.322, 0.298), pods per plant (0.443, 0.389) and pod yield per plant (0.905, 0.787) at genotypic and phenotypic levels respectively. Genotypic path analysis shows that yield per plant exhibited positive direct effect (1.138) and had strong positive association with yield per hectare (rG=0.905). The positive indirect effects were through days to 50% flowering (0.015), pods per cluster (0.035) and pod breadth (0.046). Phenotypic path coefficient shows that yield per plant had high positive direct effect (0.879) and strong degree of association (0.787) for pod yield per hectare. This direct effect is mainly due to the indirect effect of trait positively through plant height (0.043), pods per plant (0.023), pod length (0.025) and pod width (0.002). Suggesting that these parameters may be considered as prime traits during the course of selection to have the higher potential of yield in case of green gram.